2022
DOI: 10.1155/2022/9169713
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Copper Oxide Nanoparticles Incorporated in the Metal Mesh Used to Enhance the Heat Transfer Performance of the Catalytic Converter and to Reduce Emission

Abstract: Heating the catalysts chemically at a cold start is indeed an approach to achieving catalytic performance. The purpose of this effort is to reduce cold flow emissions to background levels during regular engine operation. To address this issue, a thermal model was created, and a temperature study of various configurations was performed utilizing the computational dynamics method. This was followed by a regression model to confirm the results of the experiment. The article discusses how using a computational flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the use of MCC is also reported to have an impact on engine performance. Prabhahar et al [18] reported that the use of copper in the MCC was quite effective in the oxidation process of CO and HC emissions and increased engine performance which was affected by the inlet and outlet angles of the MCC casing. According to Bell theory [19], the inlet and outlet angles of the MCC casing are designed to optimize exhaust flow by minimizing back pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of MCC is also reported to have an impact on engine performance. Prabhahar et al [18] reported that the use of copper in the MCC was quite effective in the oxidation process of CO and HC emissions and increased engine performance which was affected by the inlet and outlet angles of the MCC casing. According to Bell theory [19], the inlet and outlet angles of the MCC casing are designed to optimize exhaust flow by minimizing back pressure.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, CO emissions were reduced by 60% and NOx emissions by 70%. Additionally, copper oxide nanoparticle-based catalytic converters were tested by Prabhahar et al [4], who found that at 250°C, CO emissions were reduced by 50% and at 300°C, HC emissions were reduced by 50%. In line with the findings of previous research, Ariyanto et al [5] also proved that CO emissions were reduced by 24%, and HC emissions were reduced by 30% after using a catalytic converter made from copper-coated chrome catalytic converter on a motorcycle exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%